Preparation and Properties of Ag-Containing Diamond-Like Carbon Films by Magnetron Plasma Source Ion Implantation - K. Baba; R. Hatada; S. Flege; W. Ensinger (Advances in Materials Science and Engineering)
The doping effect of silver on the structure and properties of diamond-like carbon (DLC) films was investigated. The samples were prepared by a process combining acetylene plasma source ion implantation (high-voltage pulses of −10 kV) with reactive magnetron sputtering of an Ag disc. A mixture of two gases, argon, and acetylene was introduced into the discharge chamber as working gas for plasma formation. A negative high-voltage pulse was applied to the substrate holder, thus, accelerating ions towards the substrate. The chemical composition of the deposited films was modified by the respective gas flows and determined using X-ray photoelectron spectroscopy and secondary ion mass spectrometry. The silver concentration within the DLC films influenced the structure and the tribological properties. The surface roughness, as observed by scanning electron microscopy, increased with silver concentration. The film structure was characterized by Raman spectroscopy and X-ray diffractometry (XRD). The DLC films were mainly amorphous, containing crystalline silver, with the amount of silver depending on the process conditions. The tribological properties of the films were improved by the silver doping. The lowest friction coefficient of around 0.06 was derived at a low silver content.